Peterborough local administration : parochial government before the Reformation : Churchwardens' accounts, 1467-1573, with supplementary documents, 1107-1488 - Mellows, William Thomas (Publications of the Northamptonshire Record Society, 1939)
Transcripts of churchwardens' accounts, charters relating to town lands c. 1250-1487, documents relating to parish church and other chapels c. 1107-1398, and to the bridge, pavements and guilds 1315-1464. There are lists of parish and manorial officers, tenants, clergy, of feoffees and jurors of of the courts leet during the Civil War. the Protectorate and thereafter.